Potency of endophytic fungi from Nauclea orientalis L. as antioxidant producer - Elisa Nurnawati; Hary Widjajanti; Vivi Hendra Sutandar; Maulida Harwati; Eka Amelia; Siti Alharzsa; Nina Tanzerina (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2021)
Nauclea orientalis L. is widely distributed in Indonesia. Secondary metabolites such as flavonoids, polyphenols, and saponins are abundant in the bark of N. orientalis L. These compounds have the potential to act as antioxidants. Endophytic fungi, through genetic transfer and coevolution, can produce the same metabolites as their host plant. As a result, understanding the potential of endophytic fungi from N. orientalis L. to produce antioxidant compounds that can be developed is critical. According to the findings of this study, twelve isolates have the potential to produce secondary metabolites with antioxidant properties. Three isolates had high antioxidant activity: DB2 was identified as Aspergillus minisclerotigenes with an IC50 of 21 g/mL containing tannins, terpenes, and flavonoids, AB3 as Colletotrichum perseae with an IC50 of 31 g/mL containing tannins and terpenoids, and AB1 as Diaporthe tulliensis with an IC50 of 48 g/mL containing tannins. The secondary metabolite group has the potential to be developed into an antioxidant agent